1986
DOI: 10.1177/0310057x8601400210
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Evaluation of the Anxiolytic Properties of Intramuscular Midazolam

Abstract: The observed effect of midazolam on anxiety is equivocal in part because previous studies have not ruled out pre-treatment differences in anxiety scores between patients who received midazolam and those who did not (controls). This study re-examines the anxiolytic effect of premedication with intramuscular midazolam using a sample size calculated to be of sufficient size to rule out population differences as a variable affecting treatment results. In the midazolam group (n = 49) anxiety scores were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In two previous studies of lorazepam 2.5 or 5 mg, pronounced sedative effects were seen within one hour but still only marginal anxiolytic effect (10,13). There are also others who have failed to find any significant differences as regards anxiolysis between intramuscular premedication with other active drugs and placebo (16)(17)(18)(19)(20). In accordance with the present study both van Wijhe et al and Larsson et al found increased anxiety among more than 10% of patients after active drugs (1 9, 20).…”
Section: Discussionmentioning
confidence: 97%
“…In two previous studies of lorazepam 2.5 or 5 mg, pronounced sedative effects were seen within one hour but still only marginal anxiolytic effect (10,13). There are also others who have failed to find any significant differences as regards anxiolysis between intramuscular premedication with other active drugs and placebo (16)(17)(18)(19)(20). In accordance with the present study both van Wijhe et al and Larsson et al found increased anxiety among more than 10% of patients after active drugs (1 9, 20).…”
Section: Discussionmentioning
confidence: 97%
“…[8,27] This dosage is reported to produce adequate sedation without significantly altering blood pressure or HR. [43] In the study of Rochette et al, [44] where midazolam 0.10 mg/kg IM was premedicated in patients with mean age of 73.8 ± 8.2 years, 95% of patients experienced clinically satisfactory anxiolytic effect without adverse reactions. In the present study, however, the setting dose of midazolam was 0.07 mg/kg, the lowest dose in the recommended range, considering the physiologically reduced organ function and altered redistribution kinetics.…”
Section: Discussionmentioning
confidence: 99%